Improved hemoglobin levels with combined Fe tablets and red guava juice in anemic pregnancy - Teti Nurhayati; Lestari, Meti Widiya; Astiriyani, Endang (Jurnal Kesehatan Ibu dan Anak, 2025)
Iron deficiency anemia remains a prevalent nutritional issue among pregnant women in Indonesia. Although iron (Fe) supplementation is recommended during pregnancy, its absorption can be limited. Vitamin C, known to enhance non-heme iron absorption, is abundant in red guava juice. This study aimed to assess the effect of combining Fe tablets with red guava juice on hemoglobin (Hb) levels in pregnant women with anemia. A quasi-experimental study with a pretest-posttest control group design was conducted among 32 anemic pregnant women selected through total sampling at the Cineam Health Center, Tasikmalaya Regency. Participants were divided into an experimental group (Fe tablets + red guava juice) and a control group (Fe tablets only). The intervention was administered daily for 14 days. Hemoglobin levels were measured before and after the intervention. Data were analyzed using an independent t-test. There was a significant increase in Hb levels in the experimental group compared to the control group. The mean Hb increase in the experimental group was 0.738 g/dL (p = 0.001), indicating that the addition of red guava juice significantly enhanced the efficacy of Fe supplementation. Combining Fe tablets with red guava juice effectively improves hemoglobin levels in pregnant women with anemia. This simple and affordable dietary intervention has the potential to support maternal anemia management programs in low-resource settings.